Digital technologies in museums: New routes to engagement and participation' - Carey Jewitt (Stockholm University Press, 2012)
A multimodal semiotic approach is applied in this chapter to three examples to illustrate how the use of digital technology in museums and galleries can re-mediated the visitor experience (Jewitt, 2009; Kress, 2009). The examples are selected to expand upon the themes raised in Chapter X. They each explore different technologies, contexts and purposes and to illustrate the successful use of digital technology in exhibitions, galleries, or interventions: 1. You Tube and Flickr: The Weather Project by Olafur Eliasson at the Tate Modern Museum; 2. Interactive artefacts, virtual tours and Websites: The Winston Churchill Museum; 3. Mobile Technologies: OOLK at the D-Day museum